(untitled) (Al-Academy, 2016)
Abstract: The study of the place is hardly a concern for most researchers in the art generally. It is hardly devoid of any movie of some configuration elements that are essential to him about and place one of them, and we find an echo location consists ago to begin screenwriter put Sightseeing begins features emerge there will be functioning simple scenario what would soon receive a growing Cummings final picture film. Metaphoric place begins to emerge in the form of linguistic scenario is soon to be translated in another language, the language of the image. Which in turn complement the creative process of this art and have a significant impact in terms of content and curriculum and installation in and it even to seek the true meaning full and behind the central meaning and show the power of communication metaphoric image and the pursuit of disclosure of its structure and functions, and then the full knowledge of how to functioning within the hierarchy of the footage film. Based on this, the nature of the search warrant that the researcher by dividing the current study, five chapters, namely:1-Chapter I: stating the research problem, which was: What are the main points in which the spatial metaphor is gaining legitimacy and existence within the context of a completely different nature from any internal structure, and is it the absence of an actual place for the president?2- Chapter II: where the theoretical framework that was Includes: The first topic: the theory of interaction and metaphoric concept Film. The second topic: the spatial metaphor, functioning in the scenario.3-Chapter III: The Search procedures as adopted researcher descriptive analytical method.4- Chapter IV: analyzed a sample in which the researcher and his research was not (Shutter island) director (Martin Scorsese).5-Chapter V: Output researcher set of results from the analysis tool developed by his research. With a set of conclusions that explain the goals of his research.